Purwarupa Radar Berbasis Arduino dan GUI Processing 3 sebagai Pendeteksi Musuh - Arifin Musthofa Wasis Waskito; AL Farizi Rayhan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Radar is a tool that functions to determine the whereabouts of objects in the surroundings. A military defense system requires a system for monitoring and handling certain areas (land, sea, air) effectively and efficiently to prevent unwanted presence from entering private areas. This design is expected to increase the defense system's capabilities to make it easier to automatically track and destroy enemies. The laser gun is an actuator that is integrated to shoot enemies detected by radar. The servo motor drives the ultrasonic sensor and the diode laser which moves from 00 to 1800, the ultrasonic sensor is integrated into the servo motor which functions to detect objects by reflecting ultrasonic waves on the object and receiving them back when the waves hit the object, then the 5V diode laser is used as a weapon. will emit a laser beam when directed at an object detected by the servo motor. Processing3 software is used as a graphic programming tool that can display object detection read by the ultrasonic sensor. The results of this research are that the ultrasonic sensor is capable of detecting objects in the range 0-40cm and the servo motor is capable of reaching angles from 00 to 1800. And this system can work effectively during shooting so that it can meet defense needs in dealing with enemies and can work quickly and precisely.